Розвиток методів оцінки конкурентоздатності техніки на стадії її проектування - Тимофєєв, Дмитро Володимирович (НТУ "ХПІ", 2005)
Дисертація на здобуття наукового ступеня кандидата економічних наук за спеціальністю 08.02.02 – економіка та управління науково-технічним прогресом. – Національний технічний університет "Харківський політехнічний інститут", Харків, 2005. У дисертаційній роботі досліджені теоретико-методологічні та прикладні аспекти удосконалення та розвитку методів оцінки конкурентоздатності техніки на стадії створення й розробки її конструкції. Запропоновано нове трактування формування конкурентоздатності техніки за період її життєвого циклу, розроблено методичні основи матричного підходу до динамічної оцінки та аналізу конкурентоздатності техніки по її властивостях ресурсозбереження й задоволення конкретних потреб. Дістали подальшого розвитку методи визначення й оптимізації показників конкурентоздатності техніки на стадії її проектування, а також оцінки рівня конкурентоздатності техніки на основі прогнозування потенційного обсягу її продажу. Запропоновано основні складові системи оцінки конкурентоздатності техніки на ранній стадії її життєвого циклу.

The dissertation on competition of a scientific degree of the economic sciences’ candidate with a specialty 08.02.02 - economy and management of scientific and technical progress. - National technical university "Kharkov polytechnic institute", Kharkov, 2004. Theoretical-methodical and applied aspects of perfection and development of competitiveness estimation of technique on the development stage of its construction were investigated in dissertation’s operation. The new interpretation of formation process of engineering competitiveness in the period of its life cycle is offered; methodical bases of the matrix approach to a dynamic estimation and the analyzing of engineering competitiveness are developed according to its properties of the resources saving and special needs satisfaction. It was proposed the further techniques development of definition and optimization of parameters of engineering competitiveness at the stage of its designing, as well as the rates of engineering competitiveness on the basis of forecasting a potential sales volume. Estimation competitiveness system of engineering on early its life cycle stage is offered on a basis of a systematic approach.
Development of methods of competitiveness estimation of engineering at the stage of its designing
Keywords: конкурентоздатність; економічна ефективність; інноваційні процеси; управління НТП; ціна споживання; проектування нової техніки; автореферат дисертації; competitiveness; innovation process; management of scientific and technical progress; price of consumption; designing of new techniques; 330.341.1